Analisis dan Strategi Pengentasan Kemiskinan Di Provinsi Jambi - Ahmad Soleh (Universitas Batanghari Jambi, 2018)
The growing number of poor population is still a major problem from the Government and it is a very difficult problem to overcome. This is because it is affected by a high population growth without the availability of supported employment in addition also influenced the low HUMAN RESOURCES from the society. In percentage of visible existence of decrease in the number of poor population but in the amount of an increase in the poor population. On the basis of it then this research aims to analyze the two things are pretty important in this poverty reduction efforts among them; (1) how much poverty level happened in the provinces of Jambi and (2) the policy strategy for what could be applied in lowering poverty levels. In analyzing this problem used two approaches namely quantitative and qualitative methods to explain the results of analysis to make it more clear and easy to understand. The results showed that the number of poor population in the province of Jambi was still not stable (fluctuating) with amount still average more than 8 percent of the total population. As for the strategies that can be applied in reducing poverty can be done in a way; new economic development, microfinance institutions, and competency-based education. Keywords: Poverty, the poverty reduction Strategy.